Rapid point-of-care detection of the tuberculosis pathogen using a BlaC-specific fluorogenic probe - Xie, Hexin; Mire, Joseph; Kong, Ying; Chang, MiHee; Hassounah, Hany A.; Thornton, Chris N.; Sacchettini, James C.; Cirillo, Jeffrey D.; Rao, Jianghong (Nature chemistry, 2012)
Early diagnosis of tuberculosis can dramatically reduce both its transmission and the associated death rate. The extremely slow growth rate of the causative pathogen, Mycobacterium tuberculosis ( Mtb ), however, makes this challenging at the point of care, particularly in resource-limited settings. Here we report the use of BlaC (an enzyme naturally expressed/secreted by tubercle bacilli) as a marker and the design of BlaC-specific fluorogenic substrates as probes for Mtb detection. These probes showed an enhancement by 100–200 times in fluorescence emission on BlaC activation and a greater than 1,000-fold selectivity for BlaC over TEM-1 β-lactamase, an important factor in reducing false-positive diagnoses. Insight into the BlaC specificity was revealed by successful co-crystallization of the probe/enzyme mutant complex. A refined green fluorescent probe ( CDG-OMe ) enabled the successful detection of live pathogen in less than ten minutes, even in unprocessed human sputum. This system offers the opportunity for the rapid, accurate detection of very low numbers of Mtb for the clinical diagnosis of tuberculosis in sputum and other specimens. Rapid diagnostic methods that can be applied in resource-limited settings are important in the fight against tuberculosis. Here, fluorogenic probes are described that are activated by BlaC — an enzyme secreted by tubercle bacilli. The probes have enabled detection in unprocessed human sputum of live pathogen in less than 10 min.